Peran core self-evaluation terhadap employee creativity dimediasi knowledge sharing pada architectural employee - Farikha Auliasari; Dhiemas Trisyuananda Eniestama (Universitas Muhammadiyah Malang, 2022)
Creative industry workers in the architectural sector are required to always provide creative and innovative ideas and thoughts in their work. In this regard, it is important to increase employee creativity for creative industry workers in the architectural sector. The existence of employee creativity is inﬂuenced by the existence of core self-evaluation (CSE) owned by individuals and knowledge sharing in work. The purpose of this study was to analyze knowledge sharing as amediator of the effect of CSE on employee creativity. This study uses a quantitative research approach with purposive sampling data collection techniques. The subjects of this research are the creative industry workers in the architectural sector. The research subjects were 107 people, while the research subjects consisted of 75% men and 25% women with an age range between 20-25 years as much as 77% and 26-30 years as much as 23%. Data collection uses the Employee Creativity Scale (ECS) to measure the employee creativity variable, the Core Self-Evaluation Scale (CSES) to measure the core self-evaluation variable, and the Knowledge Sharing Scale (KSS) to measure the knowledge sharing variable. Analysis of the data in the study using the mediation analysis Process Macro Analysis. The results show that knowledge sharing partially mediates the effect of CSE on employee creativity, where when employees have a high level of CSE and apply knowledge sharing in their work, it will increase employee creativity.